Reconstruction of Murabahah Contract Schemes in Sharia Banking - Apriwandi; Paulus Sugianto Yusuf (JFBA: Journal of Financial and Behavioural Accounting, 2021)
The high level of margin in murabahah financing makes people perceive that this financing is more expensive than credit financing at conventional banks. Some other people also still think that Islamic banking is not fully sharia. The purpose of this study is to evaluate the development and practice of murabahah financing in Islamic banking today and then offer two alternatives so that Islamic bank financing products can compete competitively with credit products at conventional banks. The two alternatives offered are related to the pricing scheme and method along with the margin in this financing. This paper is a conceptual study by observing and analyzing information related to sharia banking products. In connection with the concepts or ideas presented in this paper, it contains theories and or interpretations of concepts in different ways and according to the purpose of the paper. This paper can provide a new understanding of the steps that Islamic banking needs to take to attract public interest and reach a wider range of consumers.